A comparison of existing questionnaires for identifying the causes of interstitial and rare lung diseases - Polke, Markus; Kirsten, Detlef; Teucher, Birgit; Kahn, Nicolas; Geissler, Klaus; Costabel, Ulrich; Herth, Felix; Kreuter, Michael (Respiration, 2020)
Background: A thorough diagnostic process is essential with regard to prognosis and treatment of the more than 200 different types of interstitial lung diseases (ILD). Key to this complex process is a comprehensive medical history. For this, a template is recommended and questionnaires are increasingly used. Yet, the optimal questionnaire has not been established. Objectives: We aimed to compare well-established questionnaires that are used in the diagnostic process of interstitial and rare lung diseases. Methods: Via a structured internet search and ILD expert interviews, we identified 6 different questionnaires for the diagnosis of ILDs: the questionnaires developed by the German Respiratory Society (DGP), American College of Chest Physicians (ACCP), National Jewish Health (NJH), Österreichische Röntgengesellschaft/Gesellschaft für Medizinische Radiologie und Nuklearmedizin (OERG), University of California, Los Angeles Health (UCLA), and University of California, San Francisco Medical Center (UCSF). We compared the forms, lengths, and contents of the 6 questionnaires regarding symptoms, comorbidities, drug history, previous ILD therapies, family history, smoking habits, occupational history, exposures, travel history, and former diagnostic procedures. Results: The questionnaires differed in length and content. The UCLA questionnaire focuses on connective tissue diseases extensively, while the NJH questionnaire captures previous diagnostics in detail. The OERG questionnaire is condensed, while the other 5 questionnaires are very detailed. The UCSF questionnaire contains a personal assessment part for the patient. For the majority of the questions, the patient can choose options from a preselected list of possible answers. The DGP questionnaire offers the patient the opportunity to add additional information in the form of free text to some of the key questions. Conclusions: Questionnaires are an important tool in the diagnostic process of ILDs. Further validation and adjustment to clinical guidelines will help to improve existing questionnaires. Future work must aim to develop an internationally accepted template.
Gesehen am 21.04.2020